Enhancing the electrochemical performance of LiNi0.8Co0.1Mn0.1O2 cathodes through amorphous coatings. (1st September 2022) - Dou, Lintao; Tang, Ao; Lin, Weiguang; Dong, Xin; Lu, Lu; Shang, Chaoqun; Zhang, Zhanhui; Huang, Zhiliang; Aifantis, Katerina; Hu, Pu; Xiao, Dongdong
Abstract: LiNi0.8 Co0.1 Mn0.1 O2 (NCM811) cathodes have attracted the attention of the automotive industry due to their higher capacity and operating voltage. Despite their promising electrochemical behavior, these materials do not have a stable cycling performance, as parasitic reactions take place when they come in contact with the electrolyte. Herein, amorphous Nb2 O5 is applied as a multifunctional protective layer to stabilize the NCM811 interface, resulting in reduced surface contamination (Li2 CO3 ), alleviation of transition metal (TM) ion dissolution, and suppression of surface corrosion and phase transformations during cycling. As a result, after 200 cycles, the coated NCM811 had a capacity of 180 mAh g −1 displaying an excellent capacity retention of 85.7%, which is 30% higher than that of the uncoated samples. Similarly, the Nb2 O5 coating allows for an enhanced rate capacity of 139 mAh g −1 at 5 C, compared to 117.6 mAh g −1 for the pure NCM811. In addition, the Nb2 O5 coating effectively suppresses the voltage decay with cycling, resulting in a voltage decay of 70 mV after 200 cycles, while a reduction of 190 mV takes place without the coating.